Experiences of health workers in the COVID-19 pandemic in their own words - Bismark, Marie 1973-; Lewis, Sophie 1984-; Smallwood, Natasha 1976-; Willis, Karen 1960- (The COVID-19 pandemic series, 2022)
Experiences of Health Workers in the COVID-19 Pandemic shares the stories of frontline health workers - told in their own words - during the second wave of COVID-19 in Australia. The book records the complex emotions health workers experienced as the pandemic unfolded and the challenges they faced in caring for themselves, their families, and their patients. The book shares their insights on what we can learn from the pandemic to strengthen our health system and prepare for future crises. The book draws on over 9,000 responses to a survey examining the psychological, occupational, and social impact of COVID-19 on frontline health workers. Survey participants came from all areas of the health sector, from intensive care doctors to hospital cleaners to aged care nurses, and from large metropolitan hospitals to rural primary care practices. The authors organise these free text responses thematically, creating a shared narrative of health workers experiences. Each chapter is prefaced by a commentary providing additional context and exploring the significance of the themes that emerged from the survey. This book offers a unique historical record of the experiences of thousands of healthcare workers at the height of the second wave of the pandemic and will be of great interest to anyone interested in healthcare policy and the psychological, organisational, and social challenges of the COVID-19 pandemic"--